2014
DOI: 10.1111/all.12419
|View full text |Cite
|
Sign up to set email alerts
|

Geographic and temporal variations in pollen exposure across Europe

Abstract: This is the first comprehensive study quantifying exposure to the major allergenic pollen families Betulaceae, Oleaceae, Poaceae and Asteraceae across Europe. These data can now be used for studies into patterns of sensitization and allergy to pollen and foods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(93 citation statements)
references
References 29 publications
3
90
0
Order By: Relevance
“…These airborne pollen taxa are typical for the temperate zone of Europe [13]. Thus, pollen grains of Alnus, Ambrosia, Betula, Carpinus, Corylus, Poaceae, Urticaceae, and Artemisia were found to be the most abundant in Croatia [14]. Eight pollen taxa from the top-10 pollen taxa list discussed above are represented on the list of 12 most allergenic pollen types in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…These airborne pollen taxa are typical for the temperate zone of Europe [13]. Thus, pollen grains of Alnus, Ambrosia, Betula, Carpinus, Corylus, Poaceae, Urticaceae, and Artemisia were found to be the most abundant in Croatia [14]. Eight pollen taxa from the top-10 pollen taxa list discussed above are represented on the list of 12 most allergenic pollen types in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Starting from the 1990s, episodes of pollen dispersion on regional and continental scales have been addressed in numerous studies (Belmonte et al, 2000;Corden et al, 2002;Damialis and Gioulekas, 2005;Hjelmroos, 1992;Latalova et al, 2002;Mahura et al, 2007;Ranta and Satri, 2007;Ranta et al, 2011;Rantio-Lehtimaki, 1994;Siljamo et al, 2008c;Skjøth et al, 2008;Sofiev et al, 2012bSofiev et al, , 2006aYliPanula et al, 2009; see also reviews by Smith et al, 2014, andBergmann, 2013). It was shown that, although the features of each specific long-range transport episode vary widely, there may be a systematic pattern in the springtime pollen redistribution in Europe with prevailing transport directions, main source and receptor regions, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Seasonal allergies are often characterized by the recurrence of symptoms which show periods of improvement and relapse [2]. The allergic manifestations are more prevalent during the plant pollination season; hence, accurate descriptions of its start and end periods are important for both patients and clinicians alike [3,4,5].…”
Section: Introductionmentioning
confidence: 99%